Modified silica nanoparticles stabilized foam for enhanced oil recovery - Yin, Dandan; Li, Qiuzi; Zhao, Dongfeng; Huang, Tao (Frontiers in Energy Research, 2024)
Foam has been successfully used to improve mobility control in the process of enhanced oil recovery, yet the instability of foam limits its application. Modified nanoparticles with varying wettability were prepared by reacting 3-methacryloxypropyltrimethoxysilane (KH570) with spherical SiO 2 nanoparticles in this study. Fourier transform infrared (FTIR) spectra and the measured contact angles were used to characterize the surface properties of the modified SiO 2 particles, and the foam stabilization effects of wettability SiO 2 were compared. Pore-scale visualization experiments were conducted using a 2D micromodel to identify the prevailing enhanced oil recovery (EOR) mechanisms of modified nano SiO 2 -Sodium alpha-olefin Sulfonate (AOS) foam flooding. The results indicate that modified SiO 2 effectively improves foam stability by adsorbing on the bubble surface and forming a mesh-like structure. The optimum contact angle of the particles is approximately 60°, resulting in a significant increase in drainage half-life by 29.4% compared to foam stabilized only by AOS. Additionally, Foam stabilized by modified SiO 2 demonstrates superior dynamic stability and deformation resistance. The modified SiO 2 stabilized foam exhibits enhanced interfacial viscoelasticity and plugging and profile control performance, surpassing AOS foam in displacing more residual oil in dead-end pores. The oil recovery of the micro model was determined by Image J software. KH570@SiO 2 (0.2wt%)-AOS(0.2wt%) foam flooding increased the recovery by 8.7% compared to AOS(0.2wt%) foam flooding.